2014
DOI: 10.1039/c3gc42494d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biodegradation of sugarcane bagasse by Clostridium thermocellum with surfactant addition

Abstract: SCB biodegradation and reducing sugar accumulation were remarkably increased by adding surfactant in the CBP system usingC. thermocellum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 34 publications
3
31
2
Order By: Relevance
“…The pH of those runs with a high inoculum size ( 10%) were lower than 5.0, indicating that cellulase in those systems was partly inactivated [11]. Our previous studies reported that a hydrogen production of 24.13 mmol/L was obtained with higher inoculation (10% C. thermocellum) and lower lignin-containing bagasse [21,27], indicating no significant difference with 7% inoculum size in this study. Decreases in pH during fermentation inhibit cellulose degradation, since pH affects the activity of the iron-containing cellulase enzyme [31].…”
Section: Effect Of Inoculum Size On H 2 Productioncontrasting
confidence: 65%
See 3 more Smart Citations
“…The pH of those runs with a high inoculum size ( 10%) were lower than 5.0, indicating that cellulase in those systems was partly inactivated [11]. Our previous studies reported that a hydrogen production of 24.13 mmol/L was obtained with higher inoculation (10% C. thermocellum) and lower lignin-containing bagasse [21,27], indicating no significant difference with 7% inoculum size in this study. Decreases in pH during fermentation inhibit cellulose degradation, since pH affects the activity of the iron-containing cellulase enzyme [31].…”
Section: Effect Of Inoculum Size On H 2 Productioncontrasting
confidence: 65%
“…Therefore, we predicted the substrate structure and component could have great influence on hydrogen production and substrate utilization. A similar view has been proposed in another study, which stated that the complexity of the structure was the key factor affecting the substrate degradation rate [27]. Filter paper, a kind of relatively simple cellulosic biomass, is made of cotton fiber, while SCB, a natural complex lignocellulose, is mainly composed of cellulose, hemicellulose, and lignin.…”
Section: Characterization Of Degrading Cellulosic Biomasses By C Thementioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, co-culture of C. thermocellum and Thermoanaerobacterium aotearoense can enhance the hydrogen production [1]. Besides, our studies showed that surfactant PEG8000 and CaCO3 both have positive effects on the hydrogen production by C. thermocellum [2][3][4].…”
mentioning
confidence: 64%